Modeling the theory of planned behavior to predict adults' intentions to improve oral health behaviors - Mona Talal Rajeh (BMC, 2022)
Abstract Background The present study aimed to apply the theory of planned behavior (TPB) to identify predictors of adults' intentions to improve oral health behaviors. Methods This cross-sectional study was conducted with 1,328 adults living in the Jeddah city, Saudi Arabia. A 64-item questionnaire that evaluated behavioral intention, oral health knowledge (OHK) and TPB constructs (attitudes, perceived behavioral control, and subjective norms) was distributed. Descriptive statistics and structural equation modeling (SEM) were used to describe the data and examine the associations among the variables. A p-value of < 0.05 was considered significant. Results The analysis revealed that the TPB model explained 72% of the variance in oral health behavioral intentions (OHBI), indicating a good model fit. The TPB constructs of attitudes (β = 0.299), subjective norms (β = 0.035), and perceived behavioral control (β = 0.144) were significant predictors of OHBI, whereas OHK was not. Attitude was the strongest predictor of intentions to improve oral health behaviors. Conclusions The findings suggest that this model could be a helpful framework for designing oral health promotion and intervention programs. Such programs should focus on changing adults' attitudes, positive influences from close relationships, and improving self-efficacy of OHB to improve their oral health behavior.